2014
DOI: 10.1016/j.jbusres.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Country of origin and network effects on internationalization: A comparative study of SMEs from an emerging and developed economy

Abstract: This study examines the internationalization of high technology small and medium enterprises (HTSMEs). It explores how they develop and use networks to penetrate their first foreign market relying on information collected via direct interviews with the CEOs or founders of 58 high technology small firms that operate internationally. It uses mixed methods to discuss the network building mechanisms identifiedclient supplier relationships, existing personal contacts, contacts acquired by chance, and contacts acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
160
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(173 citation statements)
references
References 61 publications
(100 reference statements)
3
160
1
9
Order By: Relevance
“…There is a dearth of empirical evidence on internationalization of ventures from Latin American emerging economies, reflected by the fact that less than 4 % of publications in major IB Journals are from Latin American authors or about a Latin American company (Biggemann 2013). Empirical evidence on internationalization of ventures from Latin American emerging economies were scare and shallow (Pérez-Batres et al 2010;Ciravegna et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…There is a dearth of empirical evidence on internationalization of ventures from Latin American emerging economies, reflected by the fact that less than 4 % of publications in major IB Journals are from Latin American authors or about a Latin American company (Biggemann 2013). Empirical evidence on internationalization of ventures from Latin American emerging economies were scare and shallow (Pérez-Batres et al 2010;Ciravegna et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Networking and learning ability were identified as the key abilities of the entrepreneurs (Ciravegna et al, 2014;Coviello, 2015;Neubert, 2016b) and the main drivers of the speed of internationalization. Several interviewees mentioned that their whole network has changed since the foundation of their high-tech startups.…”
Section: Resultsmentioning
confidence: 99%
“…To date, there is little research on born-global from emerging economies (Gonzalez-Perez et al, 2016). A study by Ciravegna, Lopez, and Kundu (2014) emphasizes the importance of social networks -particularly, the networking ability of an entrepreneur as a driver of the speed of internationalization. Hitt, Li, and Xu (2016) and Zucchella, Hagen, Denicolai, and Masucci (2016) reported that the reputation of the home country and the quality of institutions in that country also influence early and fast internationalization.…”
Section: Effect Of Location On Early and Fast Internationalizationmentioning
confidence: 99%
“…It has in fact been shown that information is crucial for more rational decision-making [8], to manage international complexity and ambiguity [29], to reduce risks and uncertainty [26], and to stimulate awareness of foreign market opportunities [30]. There are also studies on the importance of the role of information in the creation of internationalization knowledge [17,31], as well as on demonstrating that cooperation and networks are facilitators of internationalization [19,32]. In spite of this, surprisingly there is a clear lack of exploratory studies on how state-of-the-art information management models and technologies can be used to improve collaborative decision-making in the internationalization of SMEs.…”
Section: A Model Of Collaborative Network For Internationalizationmentioning
confidence: 99%